2015
DOI: 10.1002/aenm.201401801
|View full text |Cite
|
Sign up to set email alerts
|

Radical or Not Radical: Revisiting Lithium–Sulfur Electrochemistry in Nonaqueous Electrolytes

Abstract: present in DMSO solutions of lithium polysulfi des (neither S 4 ·− or S 2 ·− were detected). This was also the only radical species observed by Barchasz et al. [ 12 ] upon discharge of a sulfur electrode in tetraethylene glycol dimethyl ether (TEGDME). None of these studies, however, gives a quantitative estimate of the free radical content in the electrolyte, as compared with the various S n 2− dianions. Is the S 3 ·− radical prominent upon cycling in Li-S cells using dimethoxyethane (DME) and 1,3-dioxolane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
404
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(439 citation statements)
references
References 37 publications
19
404
2
Order By: Relevance
“…The XANES spectrum of crystalline Li 2 S exhibits the first maximum at sulfur absorption edge at 2473 eV. An additional spectral signature was described in the literature 21 with pre-edge resonances at 2468 eV, corresponding to S 3…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The XANES spectrum of crystalline Li 2 S exhibits the first maximum at sulfur absorption edge at 2473 eV. An additional spectral signature was described in the literature 21 with pre-edge resonances at 2468 eV, corresponding to S 3…”
Section: Resultsmentioning
confidence: 99%
“…Using a combination of spectral components shown in Figure 1 one can describe mechanism of sulfur conversion in different electrolytes by using a linear combination analysis (LCA). Some other contributions can be identified like formation of radicals, 21 formation of H 2 S or C-S bond due to nucleophilic reaction of polysulfides with solvent molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Furthermore, several studies have shown that the exact value of the required overpotential during the first charge of Li 2 S can be manipulated and reduced by varying the charging rate, 8,9,11 cathode morphology and structure, 9,[11][12][13][14][15] and electrolyte composition. 9,[16][17][18][19][20] The results of these recent studies, however, have not yet been incorporated into a general understanding of the charging process of Li-S batteries, and the intermediates of the initial charge of Li 2 S have * Electrochemical Society Student Member. * * Electrochemical Society Member.…”
mentioning
confidence: 99%
“…Recently, several Li-S reaction intermediates, including polysulfides, 27-29 S 3 •− , 30,31 and Li 2 S solid product, 27,32 have been shown to present unique features in the sulfur K-edge X-ray absorption near edge structure (XANES) spectrum. As a result, sulfur K-edge XANES has the potential to contribute to the understanding of the discharge mechanism in the 4-16 e -/S 8 discharge region, which is known as the low voltage plateau, and facilitate the rational design of improved Li-S batteries.…”
mentioning
confidence: 99%